2000
DOI: 10.1103/physrevlett.85.302
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Sliding Friction in Incommensurate Systems

Abstract: We study the dynamics of an incommensurate chain sliding on a periodic lattice, modeled by the Frenkel Kontorova hamiltonian with initial kinetic energy, without damping and driving terms. We show that the onset of friction is due to a novel kind of dissipative parametric resonances, involving several resonant phonons which are driven by the (dissipationless) coupling of the center of mass motion to the phonons with wavevector related to the modulating potential. We establish quantitative estimates for their e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
62
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 21 publications
3
62
0
1
Order By: Relevance
“…However, no proof has yet been available to establish the superlubric state in a practical length and time scale for real-world applications. Theoretical studies [7][8][9] show that even for atomistically smooth surfaces in contact, catastrophic breakdown of the superlubric state could occur by leaking a significant amount of kinetic energy in the mechanical motion of operation to the rest or, in other words, heat. Based on their studies on a Frenkel-Kontorova (F-K) chain model, Consoli et al [7] concluded that dissipative parametric resonance between vibrational modes in the chain results in the onset of friction in an incommensurate system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no proof has yet been available to establish the superlubric state in a practical length and time scale for real-world applications. Theoretical studies [7][8][9] show that even for atomistically smooth surfaces in contact, catastrophic breakdown of the superlubric state could occur by leaking a significant amount of kinetic energy in the mechanical motion of operation to the rest or, in other words, heat. Based on their studies on a Frenkel-Kontorova (F-K) chain model, Consoli et al [7] concluded that dissipative parametric resonance between vibrational modes in the chain results in the onset of friction in an incommensurate system.…”
mentioning
confidence: 99%
“…Theoretical studies [7][8][9] show that even for atomistically smooth surfaces in contact, catastrophic breakdown of the superlubric state could occur by leaking a significant amount of kinetic energy in the mechanical motion of operation to the rest or, in other words, heat. Based on their studies on a Frenkel-Kontorova (F-K) chain model, Consoli et al [7] concluded that dissipative parametric resonance between vibrational modes in the chain results in the onset of friction in an incommensurate system. This phenomenon was later observed in the relative sliding of concentric graphitic walls in double-walled carbon nanotubes (DWCNTs) [8], and the origin of the identified catastrophic kinetic energy leaking is attributed to the resonant coupling between the translational motion and radial breathing modes.…”
mentioning
confidence: 99%
“…-The Frenkel-Kontorova (FK) model [1] describes the interaction of a harmonic chain of atoms with a rigid substrate with period incommensurate to the lattice parameter of the chain. Its generality makes it a powerful model to investigate many different physical systems [2,3], and in particular microscopic friction between contacting surfaces [4][5][6]. The static version of the model is characterized by the Aubry transition [7], from a floating to a pinned state, for a critical value λ c of the substrate modulation potential.…”
mentioning
confidence: 99%
“…The static version of the model is characterized by the Aubry transition [7], from a floating to a pinned state, for a critical value λ c of the substrate modulation potential. Using the undamped dynamical version of this model, we addressed in previous papers the topic of "dissipation" (in the sense of transfer of energy from the center of mass to phonon modes) in incommensurate structures: we have studied the mechanism (parametric resonances) that governs the onset of sliding friction [6], and the conditions under which a new conserved quantity can be defined, which can be seen as a Generalized Angular Momentum (GAM) in the complex plane [8].In this work, we present new results, showing that, in the dynamics, a floating-to-pinned transition, analogous to the static Aubry transition, is found for all values of the potential λ < λ c . The transition is characterized by a region of critical times, with a remarkably complex behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation